Cell-based Meat: An Emerging Paradigm in Fish Meat Production: Cell-based Meat: An Emerging Paradigm in Fish Meat Production - Badireddy, Madhusudana Rao; Swaminathan, Raja, T.; Joseph, Toms, C. (Fishery Technology, 2024)
Cell-based fish meat production, an innovative  technology in its early stages in India, promises to address the fish demands of the future. This method, unlike traditional fisheries, cultivates meat directly from cells. The process begins with harvesting progenitor cells from the target fish, then differentiating and proliferating to the required numbers (either with or without scaffolds), and  finally, compacting them into meat. This technique  has the potential to create meat of all types of fishes, including threatened, endangered and non-native species. However, before cell-based meat can be commercially viable in India, it faces challenges such as production costs, consumer preferences for meat quality, and the establishment of national food safety standards, particularly as the market readies for both imported and domestically produced lab-grown fish products.